Neonatal Outcomes in Pregnant Women Infected with COVID-19 in Babol, North of Iran: A Retrospective Study with Short-Term Follow-Up. (3rd June 2021) - Akbarian-Rad, Zahra; Mojaveri, Mohsen Haghshenas; Bouzari, Zinatossadat; Sadeghi, Farzin; Yahyapour, Yousef; Rad, Mojgan Naeimi; Alizadeh, Somayeh; Ebrahimpour, Soheil; Sepidarkish, Mahdi; Javanian, Mostafa
Abstract : During the coronavirus disease 2019 (COVID-19) pandemic, the number of pregnant women and neonates suffering from COVID-19 increased. However, there is a lack of evidence on clinical characteristics and neonatal outcomes in pregnant women with COVID-19. We evaluated short-term outcomes (4 weeks postdischarge) and symptoms in neonates born to mothers infected with COVID-19. In this retrospective cohort study, we included all neonates born to pregnant women with COVID-19 admitted to Ayatollah Rohani Hospital, Babol, Iran, from February 10 to May 20, 2020. Clinical features, treatments, and neonatal outcomes were measured. Eight neonates were included in the current study. The mean gestational age and birth weight of newborns were 37 ± 3.19 weeks (30 ₊6 -40) and 3077.50 ± 697.64 gr (1720-3900), respectively. Apgar score of the first and fifth minutes in all neonates was ≥8 and ≥9 out of 10, respectively. The most clinical presentations in symptomatic neonates were respiratory distress, tachypnea, vomiting, and feeding intolerance. This manifestation and high levels of serum C-reactive protein (CRP) in three infants are common in neonatal sepsis. The blood culture in all of them was negative. They have been successfully treated with our standard treatment. Our pregnant women showed a pattern of clinical characteristics and laboratory results similar to those described for nonpregnant COVID-19 infection. This study found no evidence of intrauterine or peripartum transmission of COVID-19 from mother to her child. Furthermore, the long-term outcomes of neonates need more study.